The in vitro cytotoxic, genotoxic, oxidative damage potential of enoxaparin sodium in human peripheral blood mononuclear cells - Yıldız, Kadri (The European Research Journal, 2021)
Objectives: Enoxaparin sodium, low-molecular weight heparin (LMWH) indicated for the prophylaxis deep vein thrombosis. As far as we know, its cytotoxic, genotoxic and oxidative effects have never been studied on any cell lines. The purpose of the present study is to evaluate the in vitro cytotoxic, genotoxic damage potential and antioxidant/oxidant activity of enoxaparin sodium on primary human whole blood cultures. Methods: After exposure to different doses (from 0.5 to 100 mg/L) of enoxaparin sodium, cell viability was assessed by the cytotoxicity tests including MTT (3, (4,5-dimethylthiazol-2)-2,5-diphenyltetrazolium bromide) and lactate dehydrogenase (LDH) release assays. The antioxidant activity was measured by the total antioxidant capacity (TAC) and total oxidative stress (TOS) parameters. To determine the genotoxic damage potential, the rate of chromosomal aberrations (CAs) and 8-oxo-2'-deoxyguanosine (8-oxo-dG) levels were also assessed. Results: Cytotoxicity assays showed that treatment with enoxaparin sodium caused significant decreases in the cellular viability in a clear dose-dependent manner. Also, it was found that enoxaparin sodium did not alter the TAC and TOS levels. The genotoxicity assay showed that the formation of CAs was not observed in the lymphocytes. Likewise, the levels of 8-oxo-dG did not change in treated cultures as compared to control values. Conclusions: Enoxaparin sodium appeared to exhibit cytotoxic but not oxidative and genotoxic damage potentials in cultured human blood cells.